Severe acute interstitial nephritis induced by valsartan: A case report. Issue 6 (February 2019) - Chen, Tong; Xu, Peng-cheng; Hu, Shui-yi; Yan, Tie-kun; Jiang, Jian-Qing; Jia, Jun-ya; Wei, Li; Shang, Wen-ya
Abstract: Rationale: Angiotensin receptor blocker (ARB) can increase serum creatinine or potassium levels in patients with renal insufficiency, renal artery stenosis, heart failure or hypovolemia, but hardly cause severe kidney injury in patients without any risk factors. A case of severe acute interstitial nephritis (AIN) induced by valsartan was reported here. Patient concerns: A 62-year-old female with nausea for 1 month and acute deterioration of kidney function for 2 weeks was admitted. She had a history of hypertension for 5 months and had taken valsartan 40 mg daily for 4 months. Although the valsartan had been stopped for 2 weeks, the serum creatinine continuously increased after admission. Kidney biopsy demonstrated the eosinophils infiltration in interstitium. Diagnoses: AIN induced by valsartan. Interventions: The patient was treated with glucocorticoid. Outcomes: The serum creatinine decreased gradually and got back to normal level 5 months later. Then therapy of glucocorticoid was stopped. Renal artery stenosis was excluded by computed tomography angiography (CTA). Lessons: Although valsartan-induced allergy has been reported previously, AIN was firstly recognized as a severe complication of this drug. We suggest when there is a ARB-associated continuous deterioration of kidney function for patients without renal insufficiency, renal artery stenosis, heart failure or hypovolemia, AIN should be thought of and therapy with glucocorticoid should be considered if necessary.